Relationship between Exhaled Nitric Oxide Measured by Two Offline Methods and Bronchial Hyperresponsiveness in Japanese Adults with Asthma - Tsuburai, Takahiro; Tsurikisawa, Naomi; Morita, Sonoko; Hasunuma, Hideki; Kanegae, Hiroshi; Ishimaru, Yasushi; Fukutomi, Yuma; Tanimoto, Hidenori; Ono, Emiko; Oshikata, Chiyako; Sekiya, Kiyoshi; Otomo, Mamoru; et al. (Allergology international, 2008)
Exhaled nitric oxide (eNO) is a useful marker of eosinophilic airway inflammation in asthmatics. There have been no studies to show the relationship between eNO measured by offline methods and the degree of bronchial hyperresponsiveness in asthmatic patients treated with inhaled corticosteroids. The study population comprised asthmatics at our outpatient clinic. We measured eNO levels by two methods (“eNOs” was measured with a Sievers kit; and “eNOc” was measured with a kit from the Center for Environmental Information Science, Japan). We also used spirometry to test bronchial hyperresponsiveness to acetylcholine (PC20Ach). We recruited 192 stable asthmatics. There was a significant relationship between eNOs and eNOc (r = 0.919, p < 0.001). LogPC20Ach levels were negatively correlated with eNOs or eNOc levels (eNOs, r = −0.31, p < 0.001; eNOc, r = −0.23, p = 0.0013). We classified the subjects into two groups based on eNOs levels ((A) the subjects with high eNOs levels (n = 92) and (B) the subjects with normal eNOs levels (n = 100) ); logPC20Ach was significantly correlated with eNOs (r = −0.34, p = 0.001) or eNOc (r = −0.28, p = 0.0075) but not correlated with %FEV1 in (A), whereas logPC20Ach was not significantly correlated with eNO but significantly correlated with %FEV1 (r = 0.33, p = 0.002) in (B). Levels of eNOs and eNOc were correlated with the degree of bronchial hyperresponsiveness to acetylcholine in adult asthmatics treated with inhaled corticosteroids. Our findings suggest that offline monitoring of eNO will facilitate the management of bronchial asthma in patients treated with these drugs.